Information for contributors and readers for issue 2-2017 - Gaćeša, Nebojša N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The new Editorial Board of the Military Technical Courier Pursuant to Article 23 paragraph 2 of the Law on State Administration (Official Gazette of RS No 79/05, 101/07, 95/10 and 99/14) and point 3 of the Decision on the status of military periodicals in the Ministry of Defence, int. No 53-10 of 24th March 2006, the Minister of Defence passed the Decision on the appointment of editorial board of the Military Technical Courier (int. No 29-23) on 27th February 2017. The Editorial Board is appointed for the period of two years. More details can be seen on the journal website: http://www.vtg.mod.gov.rs/editorial-board.html.